THE EFFECT OF AUDIO-VISUAL MEDIA ON ADOLESCENTS’ KNOWLEDGE AND ATTITUDE TOWARD SMOKING DANGEROUS AT SECONDARY HIGH SCHOOL 2 HALONGONAN SUBDISTRICT, INDONESIA - Sarmaida Siregar; Kintoko Rochadi; Linda T Maas (International Journal of Nursing and Health Services (IJNHS), 2019)
Smoking is a bad behavior which can cause danger to health. Today, it becomes a habit for adolescents. It can be prevented by promoting health education by using audiovisual media, which provides information and education for increasing good knowledge and attitude toward the prevention of smoking. The research problem was how about the influence of audiovisual media on adolescents' knowledge and attitude. The objective of the research was to analyze the impact of audiovisual media on adolescents' knowledge and attitude toward the danger of smoking at SMP Negeri 2 Halongonan Timur Subdistrict. The study used a quasi-experimental method with pretest-posttest design. It was conducted at SMP Negeri 2 Halongonan Timur Subdistrict, Padang Lawas Utara Regency. Eighty-four samples were selected and allocated to the intervention group and the control group. The data were gathered using questionnaires. The hypothesis was tested by using paired t-test ad independent t-test. The result of the research showed that there was a significant influence of audiovisual media (p<0.05) on adolescents' knowledge and attitude after they had been given intervention. The conclusion was that audiovisual media was more effective in increasing adolescents' knowledge and attitude toward the danger of smoking. It is recommended that parents not smoke in front of their children. The school management needs to collaborate with the parents for discussing the academic development and students' behavior, and health care providers should increase health education program about the danger of smoking. Keywords: audiovisual media, knowledge, attitude, the danger of smoking